Um estudo sobre os gêneros textuais no apostilado de Língua Portuguesa da rede pública paulista - Barbosa, Paulo Roberto (2018)
This study deals with the analysis of issues related to the teaching of the textual genres present in the 9th Elementary School year Portuguese Language Student Notebook, a handout distributed in the public teaching system in the state of São Paulo. Its analysis was motivated by its scope and consequent relevance in the educational panorama of the state, since these handouts are used by all students. The objective that guides this research is to investigate the way in which textual genres are approached in the aforementioned in the Portuguese Language Student Notebook. This general objective is associated to the following specific objectives: to carry out a survey of the textual genres present in the handbook, relating them to their respective discursive domains; identify the typologies mobilized in the textual genres; and carry out an analysis of how and to what extent the argumentative and expository typologies can be internalized by students through proposed notebook activities. The theoretical contribution that guides the research is related to Textual Linguistics postulates, especially the intertextuality, cohesion and coherence concepts presented by the studies carried out by Fávero (2014, 2009 [1991]), Fávero and Koch (2012 [1983]) and Koch (2014 [1989], 2004, in addition to Bronckart's Sociodiscursive Interactionism (2012 [1997], 2006a), with a significant influence by Vygotsky’s (1989 1984) work. The study considers teaching based on the textual genres proposed by Bakhtin (2011 [1979]) and reinterpreted by the theoretical-methodological bias carried out by Bronckart (2012 [1997]), Marcuschi (2008) and Dolz and Schneuwly (2004), according to whom language is a form of action that takes place in the socially situated and shared discourse by means of textual genres. In this context, the present study is based on the resolutions stipulated by the National Curricular Parameters (BRASIL, 1998) regarding suggestions for the teaching of the Portuguese Language, from which the Curriculum of the State of São Paulo was developed (SÃO PAULO, 2012). These documents suggest that, in the 9th elementary school year, argumentative and expository texts should be studied with greater emphasis. In addition, this study also presents the historical course of the notebook in Brazil until its current application in the São Paulo public network. As a result of the notebook analysis, a distance was observed between what is prescribed in the State of São Paulo Curriculum and the proposed student activities concerning the learning of argumentative and exposure genres, since genres that compete in narrating were mostly inserted, while argumentative and expository genres, although appearing, were underexplored. There is, therefore, the understanding that, in order to promote the formation of socially active citizens, it is necessary to emphasize the interactive study of language, which occurs, essentially, through textual genres